Ultramodern Contraception Social Class and Family Planning in India - Alaka Malwade Basu (Harvard Center for Population and Development Studies Working Paper Series Volume 12 Number 4, 2002)
Demographers, especially when they seek to advise national governments, tend to equate successful family planning policy in the developing world with rises in what they call the `modern' methods of contraception, whether temporary or permanent. By extension, they equate `traditional' methods of contraception with traditional mentalities and insufficient motivation to control fertility. But an examination of contraceptive use patterns in one country, India, finds that in fact it is the most `modern' (those with a college education for example) women who are the most likely to use these traditional methods of birth control and to use them with great efficiency as well. It thus makes sense to question some of our standard notions of contraceptive backwardness. This paper looks at differentials in the use of traditional methods and then searches the qualitative literature to understand the preference for them among women who in principle have access to the most modern methods of birth control. It locates this preference in what may be called `ultramodern' attitudes to the body and to modern medicine. In turn, this analysis suggests that international population policy and contraceptive research may be unduly attributing contraceptive ineffectiveness to the users of traditional birth control.